Implementasi Metode Tutorial Sebaya Dalam Meningkatkan Hafalan Qur’an Santri Pondok Pesantren Darul Qur’an Kota Mojokerto - Rohman, Abdur (AL MURABBI, 2024)
A Muslim is obliged to study the Qur'an, by memorizing it. Peer tutorial method can be implemented in memorizing the Qur'an in order to obtain maximum results in terms of quality and quantity. Darul Qur'an Islamic Boarding School is one of the Islamic boarding schools combined with a private school that requires students to memorize the Al Qur'an and study general science for 6 years until graduate from high school with a minimum of 12 juz memorized. This research uses a qualitative research method with a case study approach which is based on problems that arise in the field and then studied theoretically. The implementation of peer tutorial method is carried out in pairs by tutors to students who are less skilled. Learning begins by presenting tajwid and makhroj then continues with reading half a page and repeating per waqof until memorized to meet the target of one juz in one semester. Evaluation is carried out during exam by reciting the memorization for one juz in one sitting. This peer tutorial method is successful in improving students memorization of the Qur'an in Darul Qur'an Islamic Boarding School both in terms of the quality their reading and the quantity their memorization.